The Rewriting Process in Post-War Cities - Pina Ciotoli; Rosalba Belibani (Histories of Postwar Architecture)
The drama of reconstruction is, by its very nature, linked to numerous implications of the sphere of memory and the tangible and intangible aspects of perception and enjoyment of the city. Indeed, the loss of landmarks combined with the trauma suffered brings citizens to need reconstruction for not only physical, but also emotional and psychological stability. Therefore, reconstruction, whether necessary following a war event or a natural disaster, requires reflection on the meanings of urban traces and signs, and to the role they play as identity, physical and affective references for people. Especially in the case of post-conflict reconstruction, the regeneration program must answer a long-standing question: how reconstruction and in what ways? Total reconstruction, on the one hand, tends to eliminate the trauma suffered by rebuilding the city "as it was where it was", on the other hand, selective regeneration involves the reconstruction of certain parts of a building or the selection of individual architectures, almost as if they were memory acupunctures. Places generate different forms of feeling, emotion, and memory. When discussing urban reconstruction, therefore, it is also important to reflect on the kind of affection, emotion, and remembrance that a place is able to promote, so that we can then reflect on the meanings that are more related to the sphere of memory. The theme of memory, moreover, is also central in those cases where reconstruction has failed: where  the injuries on buildings seem to have lost their deep meaning as mementos, that is, as urban monuments that, their silent presence, bear witness for future generations to the horror of war. This paper aims to offer a reflection to the theme of reconstruction understood as the regeneration of intangible (as well as tangible) urban values, trying to outline some possible scenarios with respect to the recent destructions in the city of Irpin in Ukraine.